MANAJEMEN BANDWIDTH DENGAN SIMPLE QUEUE DAN QUEUE TREE DI LABORATORIUM KOMPUTER UNIVERSITAS SAHID SURAKARTA - Widayanto, Amri Eka; Susilo, Dahlan; AL Haris, Firdhaus Hari Saputro (JURNAL GAUNG INFORMATIKA, 2016)
In 2016, Sahid Surakarta University uses internet access with bandwidth capacity  of 15 Mbps, it is obtained from the internet service provider (ISP) and uses Mikrotik  Router as a server. Through bandwidth capacity increasing, the allocation for computer  laboratory also increased to 2 Mbps so it needs proper bandwidth management that the  distribution of bandwidth separates all the computers at the computer laboratory  equally. The methods of the research were observation, interview, and review the  literatures before implementation. This research was carried out for comparative analysis of two queuing technique. They are Simple Queue and Queue Tree with  Hierarchical Token Bucket (HTB) system. Besides the implementation uses Mikrotik  Router OS, the comparison was performed based on four parameters of Quality of  Service (QoS) in TIPHON standard, they are throughput, delay , jitter, and packet loss.   Tests was performed by 5 client with 5 times of testing for each client. Data collecting  was implemented to determine the value of the QoS parameters by Wireshark Network  Analyzer when download and upload data simultaneously on an FTP server using  FileZilla Client. The results Simple Queue and Queue Tree when uploading data produces a  satisfactory value with the index 3.5. Throughput value for Simple Queue and Queue Tree is 75%. Simple Queue has the advantage on delay and jitter parameters, it is 55.11  ms (Simple Queue) than 55.47 ms (Queue Tree) for delay and 55.10 ms (Simple Queue)   than 55.46 ms (Queue Tree) for jitter. The results queuing system when download is  higher than the upload that is 3.75. It includes a category satisfying. Simple Queue has  an advantage in throughput (84%), delay (28.72 ms), and jitter (28.72 ms), Queue Tree  has a throughput value (81%), delay (29.72 ms), and jitter (29 , 72 ms).